Effects of crude humin from selected waste composts on ammonia volatilization and maize (Zea mays L.) cultivation - Perumal, Palanivell (2012)
Waste from oil palm plantations, paddy fields, sawn timber and poultries are substantial. Inappropriate disposal of these wastes can cause environmental problems such as air and land pollution. These problems can be reduced by recycling the wastes through composting. Compost has been used widely to supply nutrients, organic matter into the soil and improves soil physical characteristics. Compost also contains beneficial humic fractions such as humic acids (HA), crude fulvic acids (CFA) and crude humin (CH). Thus, this study was conducted to produce good quality compost and CH as well as to determine the effect of mixing CH with urea and Egyptian rock phosphate (ERP) on ammonia (CH3) volatilization and selected soil chemical properties. Furthermore, this study was conducted to evaluate the effects of CH and compost on maize growth, nutrient uptake and use efficiency. Composting of rice straw, rice husk, sawdust and palm oil empty fruit bunch (EFB) were carried out in 48 × 35.5 × 34.7 cm sized white polystyrene box. Then, HA, CFA and CH were extracted from compost using standard methods. Standard procedures were also used to analyze compost, HA, CFA and CH. Rice straw compost had higher ash, nitrogen (N), phosphorus (P), cation exchange capacity (CEC), humic acids (HA), potassium (K) and iron (Fe) contents with lower organic matter (OM), total organic carbon (TOC), C/N and C/P ratio compared to other composts. Sawdust compost HA had higher C, carboxylic, K and Ca content compared to other HA. Crude FA from rice straw compost had highest pH, total K, calcium (Ca), magnesium (Mg) and sodium (Na) contents compared to other CFA. Crude humin from rice straw compost had higher content of ash, N, P and CEC compared to other CH. Humification and mineralization of compost could be the reason for these findings. As reported by researchers, higher humification and mineralization produces high quality compost and HA, which promote higher amount of nutrient content and CEC. Hence, rice straw produced good quality compost, CFA and CH while sawdust compost produced good quality HA. Ammonia (NH3) loss study was carried out using the closed-dynamic air flow system. Four different CH were mixed with urea and ERP before applied on the surface of the soil. Standard procedures were used to determine NH3 loss and selected soil chemical properties of incubated soils. Amending urea with CH had no effect on total amount of NH3 loss. But, addition of the CH significantly increased pH, OM, TOC, CEC and exchangeable cations of Typic Paleudults. Hence, CH from selected waste compost can be used to improve soil chemical properties. A pot study with ten treatments was conducted under rain shelter. Standard procedures were used to determine selected soil chemical properties before and after planting. The plants were measured for stem diameter and height at tasselling stage prior to harvest. Dry matter production, nutrient uptake and nutrient use efficiency were also measured. Application of sawdust compost (T8) significantly increased maize plant diameter, height, dry matter production, and N, P and K uptake and use efficiency compared to T1 (chemical fertilizer). In treatment T8, sawdust compost supplies 1.2 g HA kg-1 soil which increased the nutrient uptake and use efficiency and this observation was consistent with previous study. Hence, sawdust compost (T8) is superior in maize plant growth, nutrient uptake and use efficiency compared to chemical fertilizer and it also reduced usage of N, P and K based chemical fertilizer up to 90%. Application of CH and selected waste composts (rice straw, rice husk and EFB) could be used as an alternative for chemical fertilizers due to their similar effects on maize plants.